José Ramón González, Virginia Martín Jiménez, Susana Gil-Albarellos y Alejandro Alonso Nogueira (2016): Testimonios del desastre. Periodistas y escritores en los campos de batalla - Sáez Vázquez, Esperanza (RIHC. Revista Internacional de Historia de la Comunicación, 2016)
Testimonios del desastre. Periodistas y escritores en los campos de batalla José Ramón González, Virginia Martín Jiménez, Susana Gil-Albarellos Pérez-Pedrero, Alejandro Alonso Nogueira (EDS.) Editorial Trea, Gijón, 2016 381 pp.